Analisis Kepuasan Pasien Terhadap Kualitas Pelayanan Rawat Jalan Rumah Sakit X Menggunakan Service Quality Metode Costumer Statisfaction Index (CSI) dan Importance Performance Analysis (IPA) - Saputri, Anggi Lisa; Lubis, Fitriani Surayya; Suherman, Suherman; Nazaruddin, Nazaruddin; Nur, Muhammad (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This study aims to evaluate the level of customer satisfaction with outpatient services at Hospital X and identify areas that require improvement. The results of data processing show that the customer satisfaction index (CSI) value obtained is 76.435%, which is included in the "Satisfied" category. However, there are still a number of patients who are dissatisfied with the services they receive, so efforts are needed to improve the quality of outpatient services. Meanwhile, the results of further analysis using the importance performance analysis (IPA) method reveal attributes that require special attention. The attributes are in Quadrant I of the Cartesian IPA diagram, which shows improvement priorities. Recommendations for improvement include adding facilities such as drinking water stations, children's play areas, and spare chairs for patients queuing. Apart from that, it is necessary to design standard operating procedures (SOP) that are in accordance with doctors' schedules to avoid schedule conflicts, as well as regular training regarding service excellence for medical personnel and hospital staff. The implementation of these recommendations is expected to increase patient satisfaction with outpatient services at Hospital X.